Antibiotic Prophylaxis, Immunoglobulin Substitution and Supportive Measures Prevent Infections in MECP2 Duplication Syndrome. Issue 5 (May 2018) - Bauer, Michael; Krüger, Renate; Kölsch, Uwe; Unterwalder, Nadine; Meisel, Christian; Wahn, Volker; von Bernuth, Horst
Abstract : Respiratory infections are the main cause of early death in patients with MECP2 duplication syndrome. We report on a 20-year-old patient with MECP2 duplication syndrome, IgG2/IgG4/IgA/IgM deficiency and polysaccharide-specific antibody deficiency, who had 46 episodes of pneumonia in his first 13 8/12 years of life. Immunoglobulin substitution, daily antibiotic prophylaxis with two agents and supportive measures reduced occurrence of pneumonia to four episodes in the following 6 2/12 years of life.